WHAT DOES THE ACADEMY MEAN BY “NEOLIBERALISM”? REFLECTIONS ON A CONCEPT - Flórez-Estrada Pimentel, María (2022)
In this article, I reconstruct and analyze the epistemic changes produced by liberalism and the development of capitalism in Modernity, which significantly altered the identities of men and women, the social imaginary about social and kinship relations, as well as the horizon of possibilities. In addition, I critically review the genealogy of the concept of “neoliberalism” in order to problematize its use by Academia and recover the usefulness of liberal ideas and values for feminism and for the women organizations, which, in the 21st. Century, they continue to struggle in order to obtain basic rights, such as the right to work under equal conditions.